Editorial (American Journal of Islam and Society, 2006)
In this issue, we move away from our customary focus on the MuslimMiddle East and Muslims in the West and turn toward Southeast Asia andChina. Here, we find Muslim communities that seem not to be so entrancedby what we in the West consider to be the most pressing issues: the Muslimworld vs. the West and/or modernity, the Abrahamic faiths trialogue, politicaland economic reform, the suitability of western-style democracy inMuslim countries, and the rise of Islamic “fundamentalism,” “terrorism,”“extremism,” or whatever similar term the media throws at us.Excluding Indonesia and Malaysia, the overriding concerns of theseMuslims appear to be different, for they are often viewed as unwanted orignored minority communities. For example, Muslims living in Xinjiang,southern Thailand, and the southern Philippines are confronted daily by hostileor indifferent regimes that want their natural resources and land. Thus,their main concerns are actual (as opposed to theoretical) justice, beingallowed to remain “different” instead of being forced to assimilate, and passingon their religious and cultural identities in a hostile environment.In interfaith terms, their intellectuals are involved in other discourses:Islam and Buddhism, Confucianism, communism, folk religion, cultural chauvinism,and others. To cite an example, one of my Cham Muslim friends fromVietnam translated the Qur’an into Vietnamese several years ago. Accordingto him, the hardest part was translating such monotheistic concepts as God,sin, final judgment, good, and evil into a non-monotheistic language that hasno words for such concepts. One of our articles (Peterson) deals with howChinese Muslim scholars of the pre-modern era tried to solve this problem.Several of our articles deal with China, whose rite of passage intomodernity might have killed a lesser nation. Within the space of 100 years,it was ruled by a highly traditional empire engulfed in its own hubris, anationalist republican regime beset by a virulent communist insurgency andJapanese invasion, and an extremely radical revolutionary communistregime. And now it is an economic dynamo, due to its “capitalism with Chinesecharacteristics.” But what do we know of its Muslims, other than thatthe Turkic Muslims of Xinjiang continue to be restive and that the Bushadministration has accepted Beijing’s claim that several of Xinjiang’s secessionistgroups have links with the Taliban and al-Qaeda? ...